3D Back Analysis of Karyamekar Landslide, West Java, Indonesia: Effects of Tension Crack and Rainfall on Peak and Residual Soil Shear Strength - Aisya Galuh Laksita; Fikri Faris; Ahmad Rifa’i (Journal of the Civil Engineering Forum, 2023)
A landslide was experienced in Karyamekar Village, Cilawu District, Garut Regency, West Java, on 12 February 2021 at approximately 300 m length with a depth of 20 m, leading to a steep slope. Therefore, this study aimed to use 3D back analysis to determine soil shear strength to be subsequently applied in analyzing the possibility of further landslide with due consideration for tension crack and rainfall effect. It was also used to understand the influence of these factors on slope stability. Filled tension crack and rainfall effects were modeled using Finite Element Method (FEM) while Limit Equilibrium Method (LEM) was applied for back analysis. The results of back analysis showed that peak shear strength value of φ was 31.18° at a cohesion of 8.01 kPa while the residual shear strength value of φ was 10.35° with 2.31 kPa. The φpeak value was found to be close to the estimated 32°, but there was a significant difference in the φresidual which was approximated to be 30°. This discrepancy could be attributed to several factors such as the accuracy of rainfall data and geometry as well as the absence of some soil samples during the investigation. The cohesion values for peak and residual soil shear strength were considered acceptable because of the smaller values compared to the typical cohesion of SM (Silty Sand) which was set at 20°. Moreover, slope stability analyses conducted using only the effect of tension crack produced a safety factor of 0.996 while those with only the effect of rainfall had 1.172. The results showed that water pressure in tension crack had a more significant influence on slope stability compared to rain. However, it was important to state that the variation in the significance of each factor was based on the assumptions made during the analysis.